Traversing B/Orders of English in the Academic Writing Classroom - Baus, Dunja; Bohórquez, Paola (Tusaaji: A Translation Review, 2017)
In line with current discussions in the field of critical composition studies urging us to identify pedagogical approaches that engage the multilingual and multidialectal competencies of our students, this paper mines the pedagogical potential of the concept of translation in the composition classroom. Specifically, it presents a pedagogical exercise in intralingual translation that asks students to explicitly and deliberately place Standard English in conversation—and in tension—with varieties of English drawn from their own linguistic repertoires. Through a close reading of the students’ translative practices, we showcase their compositional competencies as they engage with and transform the rhetorical, stylistic, and grammatical registers of the source text.